Strength training and endurance performance - Seiler, S.
In endurance performance, we are limited by weak links in the physiological system. Making an already strong link stronger doesn't keep a chain from breaking if you still have the same weak link. Throughout the MAPP, I have repeatedly discussed maximal oxygen consumption, lactate threshold and efficiency of movement as major components of any endurance performance. We have talked about the heart and how it responds to training. We have discussed the skeletal muscles and their primary adaptations. Now I want to think out-loud a little bit about how, or IF strength training fits into the endurance athlete's training program. First let's define strength training. For the endurance athlete, I will call any exercise that is designed to increase the size and/or maximal strength of a muscle or group of muscles strength training. Many endurance athletes are lifting weights 2 to 3 times per week and swear by it. Others never lift a weight and excel. Second, let's make sure we understand that strength training for health versus strength training for enhanced performance are two different beasts. I think there are excellent reasons to strength train for health. As we age (especially beyond 50 or so) our bodies tend to lose muscle mass. Retarding this change is definitely beneficial. Maintained or increased muscle mass helps to prevent body fat accumulation, maintain functional mobility, decrease risk of adult onset diabetes etc. From here out I am speaking only about PERFORMANCE!